Influence of various parameters in the seismic soil-structure interaction response of a nuclear power plant. (15th August 2020) - de Borbón, Fernanda; Domizio, Martín; Ambrosini, Daniel; Curadelli, Oscar
Highlights: Soil structure interaction of CAREM-25 NPP is studied. Full 3D coupled numerical model was developed. Influence of soil stiffness, 3SI and infill soil are studied. Modeling guidelines for SSI and 3SI of NPP are recommended. Important reductions of accelerations for flexible soil are obtained. Abstract: This paper presents a numerical study of the influence of various parameters on the seismic response of the CAREM-25 nuclear power plant (NPP) located in Argentina. The influence of soil stiffness, structure-soil-structure interaction (3SI), and infill soil stiffness are studied. Considering the available analysis capabilities, a full 3D methodology was adopted (direct method). Two soil profiles were used in order to quantify the influence of the soil on the structural response. An engineered rockfill was also used in order to study the influence of infill soil stiffness. Three artificial records with three components each were used as free field input. These records were obtained from the site design spectra. The turbo-group building was approximately modelled in order to consider 3SI. Finally, all live loads as well as the water in pools were included in the model. Design guides for this type of problem are given for all the elements of the model. When comparing flexible soil with stiff soil, important reductions of the maximum absolute acceleration value are obtained by flexible soil. Moreover, the horizontal maximum accelerations are remarkably amplified in height in the case of stiff soil. The influence of the proximity of the turbo-group building (3SI) on the dynamic response of the reactor building is negligible. Finally, the influence of infill soil stiffness is also negligible.